ЧЕТ ТИЛИ ТАЪЛИМИДА ИЖТИМОИЙ-МАДАНИЙ КОМПЕТЕНЦИЯНИ РИВОЖЛАНТИРИШДА ТИНГЛАБ ТУШИНИШНИНГ АҲАМИЯТИ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article is dedicated to the use of songs as one of the effective methods in foreign language classes.
Keywords: culture, motivation, song, method, music, language.